2012
DOI: 10.5430/wje.v2n2p2
|View full text |Cite
|
Sign up to set email alerts
|

Embarking on the Teaching Journey:Pre-service Teachers Reflecting upon Themselves as Future Teachers

Abstract: This article reports on a research study that examined 25 reflective papers written by pre-service teachers a few weeks into attending primary teacher education. The overall aim of the study was to gain insight into the students' thoughts and ways of reflecting as a basis for taking action to improve lecturing, tasks and exercises which promote reflection in the primary teacher education program. The students were asked to write a paper reflecting upon "The teacher I want to become". Two research questions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
5
0
1
Order By: Relevance
“…At the same time, Ariel highlighted his desire to devote himself to the students' development. The great emphasis toward students portrayed by pre-service teachers in visual narratives was also reported by previous studies (Chang-Kredl & Kingsley, 2014;Dinham et al, 2017;Lyngsnes, 2012). For instance, other study outlined that the nature of pre-service teachers' visual narratives that incorporated direct smiles, open stances, and positive written remarks represent the pre-service's attitudes that the sense of caring was important for their future practices with their students (Dinham et al, 2017).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…At the same time, Ariel highlighted his desire to devote himself to the students' development. The great emphasis toward students portrayed by pre-service teachers in visual narratives was also reported by previous studies (Chang-Kredl & Kingsley, 2014;Dinham et al, 2017;Lyngsnes, 2012). For instance, other study outlined that the nature of pre-service teachers' visual narratives that incorporated direct smiles, open stances, and positive written remarks represent the pre-service's attitudes that the sense of caring was important for their future practices with their students (Dinham et al, 2017).…”
Section: Discussionsupporting
confidence: 60%
“…They discovered that the future selves imagined by the teacher candidates were informed as a response to what they previously witnessed and experienced that were related to diversity and inclusivity. Other study supported statement by state in projecting their future imaginations, pre-service teachers are incline to either provide their future students of what they did not experience previously or enhance what they felt positively during their previous schooling experience (Lyngsnes, 2012).…”
Section: Discussionmentioning
confidence: 80%
“…As stated, reflective teachers improved their social associations among students, felt higher job fulfillment and outlooks of self-efficacy, became more expressive on their experiences written and non-written, and anticipate themselves and their students to act uprightly. The vital part of reflective thinking in recognizing, analyzing, and unraveling the multifaceted difficulties and challenges faced by teachers in their career were suggested by Lyngsnes (2012). This notion was supported by Postholm (2008) who defined reflection as the fundamental component to the learning and improvement of teaching practice.…”
Section: Main Textmentioning
confidence: 99%
“…Dos and Demir (2013), and Lyngsnes (2012) similarly reported that several of the students' reflective outputs in their separate studies manifested descriptive writing. It is apparent that when students are assigned to produce reflective writing, their outputs include description type of reflective writing.…”
Section: Description Typementioning
confidence: 99%
“…At the peak of reflective writing is critical reflection, wherein reflections of multiple perspectives are situated in the context of historical and socio-political influences. This model has been used and adapted to analyze and identify types of reflective writing (e.g., Dos & Demir, 2013;Estrada & Rahman, 2014;Kocoglu, Akyel, & Ercetin, 2008;Lyngsnes, 2012;Marcolino & Mizukami, 2008;Ming & Manaf, 2014;Prestridge, 2014).…”
Section: Hatton and Smith's Types Of Reflective Writingmentioning
confidence: 99%